Social Projection of Law: PROSODE, a Contribution of Projection and Social Responsibility - Ortiz Sanchez, Iván (2010)
The author emphasizes that the student of the specialty of Law must be the protagonist in his own learning. For this, it is important to link the social reality in which their legal skills are used under the supervision of a professor. As a consequence of this, it is intended to consolidate a comprehensive, humanistic education and formation of ethical principles. Therefore, the objective of this article is to show the contribution of PROSODE towards social responsibility in the Faculty of Law of the PUCP. In this way, the article will begin to develop the concept of university social responsibility considering four lines of institutional action: internal management, teaching, research, social projection. Second, a review of the background and formation of PROSODE is made, in which two types of objective stand out. On the one hand, it is oriented towards the learning and personal development of the student. On the other hand, it focuses on the quality of the service provided to the beneficiary population to facilitate access to justice, the defense of human rights and citizen education. Third, the methodology of the course of which was used is developed: problem-based learning (ABP), service-learning and essentially the clinical method. Fourth, the areas of application of PROSODE will be shown, which include: legal advice, legal education, legal diffusion and the penal-penitentiary area. Finally, the impact on students and the community is shown. To do this, they will be based on interviews, statistical data and other data. In short, it is stated that it is necessary to consolidate a mandatory proposal for the PROSODE course at the Faculty of Law, since it has traditionally been of a voluntary nature. All this will help future professionals to exercise their profession with the appropriate skills, attitudes and ethical principles.